Enhancing digital literacy in Thai higher education: A strategic imperative - Noppakhunwong, Thaksina; Kantathanawat, Thiyaporn; Pimdee, Paitoon (Edelweiss Applied Science and Technology, 2025)
This study aims to enhance digital literacy in Thai higher education through the development of an integrated framework—3CLPC (Cloud-based, Collaborative, and Positive Coaching). A mixed-methods approach was employed, combining surveys and interviews with students and faculty from three public universities. Quantitative data were analyzed using descriptive statistics, while qualitative input informed iterative model refinement. The results indicated improvements in students’ digital competencies, especially in collaboration, content creation, and problem-solving. Participants also reported increased confidence and engagement when using cloud-based tools and receiving supportive coaching. The 3CLPC framework effectively addresses the divide between access to technology and pedagogical effectiveness, particularly in under-resourced institutions. The model is scalable and adaptable to other Southeast Asian contexts. Practical implications include integration into teacher training programs and digital curriculum policies. The study contributes to bridging the gap between policy and practice in digital education, emphasizing equity and learner-centered design.